Broad-based black economic empowerment : the holy grail for financial health? A study of companies listed on the Johannesburg Stock Exchange - Dreyer, Jan Adriaan (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.